Identifikasi Bakteri Pereduksi Logam Pb dalam Bioremediasi Sampel Air Sungai Citarum Menggunakan Analisis Gen 16s rRNA: Identification of Pb Metal Reducting Bacteria in Bioremediation from Citarum River Water Samples Using 16s rRNA Gene Analysis - Ni'matul Murtafi'ah; Suci Rizki Nurul Aeni (Borneo Journal of Medical Laboratory Technology, 2023)
The bioremediation technique is an effort to remove the heavy metal Pb in samples of Citarum river water. High concentrations of heavy metals harm the environment, so Pb metal-reducing bacteria are needed as a pollution solution. Bioremediation uses bacteria. Bacteria are identified by molecular methods, namely sequencing analysis techniques, because they are more accurate. To determine the nucleotide sequence of Pb metal-reducing bacteria isolates and which bacterial species can reduce Pb metal. The methodology used is primary data collection, namely conducting research directly, namely the stages of bacterial purification through gram staining techniques, pure colonies, then proceeding to the DNA isolation stage. The isolated DNA is then electrophoresed. The electrophoresis results are then purified and proceed to the sequencing stage. The feasibility test results were to obtain pure DNA from the reducing bacteria. The next step was PCR amplification of the 16S rRNA gene of Pb-reducing bacteria. The research results started at the DNA isolation stage and obtained a purity of 1.80. The PCR results were in the form of amplification of the 16S rRNA gene of Pb-reducing bacteria. Electrophoresis obtained the results of DNA bands measuring ± 1400 bp—phylogenetic tree analysis with 99.60% relatedness to Bacillus cereus, which can reduce Pb. Bacillus cereus species can carry out detoxification mechanisms against the toxic effects of Pb metals, such as—biosorption, bioaccumulation, reduction, solubilization, precipitation (formation of extracellular complexes), and methylation.